KEANEKARAGAMAN DAN POTENSI FLORA DI CAGAR ALAM PEGUNUNGAN CYCLOPS, PAPUA - Uji, Tahan (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
Study on richness, diversity and potential species of plant in two location in the Pegunungan Cyclops Nature Reserve had been conducted. One hundred and fifty species of plant are collected from this area, and 75 species of them are reported as potential species. The largest group of potential species is medicinal plants (35 species) follows by timber (33 species), ornamental plants (22 species), vegetables (16 species), and fruits (10 species). The results of study recommended that buah merah (Pandanus conoideus), matoa (Pometia pinnata) , tongkeu (Aidia racemosa), oi nokom (Parastemon urophyllus), and kayu besi (Instia bijuga) were very important as potential species of plants; and also reported that kreipeh (Saccharum officinarum) is a potential geneticresources of the wild sugar plants in Cagar Alam Pegunungan Cyclops.